Preserving The Retrieval Option In The Design Of High-Level Waste Repository - N. S. Tanious (Society for Mining, Metallurgy & Exploration, 1989)
Retrievability of emplaced nuclear waste from the geologic repository is a performance objective imposed by Federal Regulations. This requirement is designed to provide confidence in the Department of Energy's repository design by keeping the option of retrieval open if the engineered or natural systems prove inadequate for containment and long-term isolation of high-level nuclear waste. This paper presents a summary of current Nuclear Regulatory Commission Staff thinking on the design of the repository for retrieval, and level of retrievability demonstration that may be required during site characterization. However, this paper does not represent official U.S. Nuclear Regulatory Commission position on this topic.